1999
DOI: 10.1097/00004714-199908000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Social Phobia With Gabapentin

Abstract: A randomized, double-blind, placebo-controlled, parallel-group study was conducted to evaluate the efficacy and safety of gabapentin in relieving the symptoms of social phobia. Sixty-nine patients were randomly assigned to receive double-blind treatment with either gabapentin (dosed flexibly between 900 and 3,600 mg daily in three divided doses) or placebo for 14 weeks. A significant reduction (p < 0.05) in the symptoms of social phobia was observed among patients on gabapentin compared with those on placebo a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
136
1
2

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 361 publications
(142 citation statements)
references
References 27 publications
1
136
1
2
Order By: Relevance
“…shown to be effective in SAD in DBPC studies (Pande et al 1999(Pande et al , 2004. In an unpublished study, pregabalin was not effective in SAD.…”
Section: )(C1) á Both Gabapentin (B) and Pregabalin (D) Werementioning
confidence: 93%
See 2 more Smart Citations
“…shown to be effective in SAD in DBPC studies (Pande et al 1999(Pande et al , 2004. In an unpublished study, pregabalin was not effective in SAD.…”
Section: )(C1) á Both Gabapentin (B) and Pregabalin (D) Werementioning
confidence: 93%
“…In comparator studies, it was more effective than placebo and as effective as pregabalin (Montgomery et al 2006b) and duloxetine (Hartford et al 2007;Nicolini et al 2008). In a further comparator study, it was more effective than buspirone (Davidson et al 1999); however, scores were only significantly lower for HAM-A psychic anxiety factor, anxious mood, and tension, but not for HAM-A total and CGI for venlafaxinetreated patients than for placebo-treated patients. In a study with diazepam as active control, the benzodiazepine was significantly superior to placebo, but neither dose of venlafaxine-XR was different from placebo on HAM-A total score (Hackett et al 2003).…”
Section: Generalized Anxiety Disorder (Gad)mentioning
confidence: 95%
See 1 more Smart Citation
“…40 -42 For example, in a study of patients with social phobia, those treated with gabapentin (n ϭ 34) showed a significantly greater reduction in scores on the Liebowitz Social Anxiety Scale compared with placebo recipients (n ϭ 35; p ϭ 0.008). 40 Animal studies and several small, uncontrolled clinical trials show that gabapentin may reduce alcohol withdrawal symptoms. In a comparison with phenobarbital, the severity of alcohol withdrawal craving decreased at similar rates in both treatment groups.…”
Section: Gabapentinmentioning
confidence: 99%
“…14 Apart from its use in bipolar disorder, gabapentin has been used in patients with anxiety, panic disorder, social phobia, aggressive behavior, and posttraumatic stress disorder (PTSD). [15][16][17][18][19][20][21] Gabapentin has also been used in treating obsessive-compulsive disorder. 15,22,23 Other areas of clinical use have been in the treatment of substance abuse disorders [24][25][26][27] and in the treatment of agitation and disruptive behavior in Alzheimer's disease.…”
Section: Psychiatric Uses Of Newer Anticonvulsantsmentioning
confidence: 99%